84.3k views
1 vote

(1)/(2) √(48) -5√(147) -\sqrt{108

User Stew
by
4.9k points

1 Answer

1 vote

Answer:


-39√(3)

Explanation:

Given expression:


(1)/(2)√(48)-5√(147)-√(108)

Rewrite 48 as 4²·3, 147 as 7²·3 and 108 as 6²·3:


\implies (1)/(2)√(4^2 \cdot 3)-5√(7^2 \cdot 3)-√(6^2 \cdot 3)


\textsf{Apply radical rule} \quad √(ab)=√(a)√(b):


\implies (1)/(2)√(4^2) √(3)-5√(7^2) √(3)-√(6^2) √(3)


\textsf{Apply radical rule} \quad √(a^2)=a, \quad a \geq 0:


\implies (1)/(2)\cdot 4} √(3)-5\cdot7 √(3)-6 √(3)

Simplify:


\implies 2 √(3)-35 √(3)-6 √(3)

Factor out the common term √3:


\implies (2 -35-6) √(3)

Carry out the subtraction inside the parentheses:


\implies -39√(3)

User Etarion
by
5.4k points